Mobile wireless-controlled vacuum cleaner - Mohammed Rabea Taleb Banalzwaa, 1993- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2018